In Enterovirus 71 Encephalitis With Cardio-Respiratory Compromise, Elevated Interleukin 1β, Interleukin 1 Receptor Antagonist, and Granulocyte Colony-Stimulating Factor Levels Are Markers of Poor Prognosis - Griffiths, Michael J.; Ooi, Mong H.; Wong, See Chang; Mohan, Anand; Podin, Yuwana; Perera, David; Chieng, Chae H.; Tio, Phaik Hooi; Cardosa, Mary Jane; Solomon, Tom (Oxford Journals, 2012)
Background. Enterovirus 71 (EV71) causes large outbreaks of hand, foot, and mouth disease (HFMD), with severe neurological complications and cardio-respiratory compromise, but the pathogenesis is poorly understood.